One million haemopoietic stem-cell transplants: a retrospective observational study. Issue 3 (March 2015) - Gratwohl, Alois; Pasquini, Marcelo C; Aljurf, Mahmoud; Atsuta, Yoshiko; Baldomero, Helen; Foeken, Lydia; Gratwohl, Michael; Bouzas, Luis Fernando; Confer, Dennis; Frauendorfer, Karl; Gluckman, Eliane; Greinix, Hildegard; et al.
Summary: Background: The transplantation of cells, tissues, and organs has been recognised by WHO as an important medical task for its member states; however, information about how to best organise transplantation is scarce. We aimed to document the activity worldwide from the beginning of transplantation and search for region adapted indications and associations between transplant rates and macroeconomics. Methods: Between Jan 1, 2006, and Dec 31, 2014, the Worldwide Network for Blood and Marrow Transplantation collected data for the evolution of haemopoietic stem-cell transplantation (HSCT) activity and volunteer donors in the 194 WHO member states. Findings: 953 651 HSCTs (553 350 [58%] autologous and 400 301 [42%] allogeneic) were reported by 1516 transplant centres from 75 countries. No transplants were done in countries with fewer than 300 000 inhabitants, a surface area less than 700 km 2, and a gross national income per person of US1260 or lower. Use of HSCT increased from the first transplant in 1957 to almost 10 000 by 1985. We recorded a cumulative total of about 100 000 transplants by 1995, and an estimated 1 million by December, 2012. Unrelated donor registries contributed 22·3 million typed volunteer donors and 645 646 cord blood products by 2012. Numbers of allogeneic HSCTs increased in the past 35 years with no signs of saturation ( R 2 =0·989). Transplant rates were higher in countries with more resources, more transplant teams, and an unrelated donor infrastructure. Interpretation: Our findings show achievements and high unmet needs and give guidance for decisions; to grant access for patients, to provide a donor infrastructure, and to limit overuse by defining risk and region adapted indications for HSCT as an efficient and cost-effective approach for life-threatening, potentially curable diseases. Funding: Funding for this study was indirectly provided by support of the WBMT.